Scale of institutional public procurement of food in Brazil - Rovane Battaglin Schwengber; Eduardo Pontual Ribeiro; Fábio Veras Soares; Rodrigo Octávio Orair (International Policy Centre for Inclusive Growth (IPC-IG), 2015)
A majority of people living in rural areas depend on agriculture for their livelihoods. Investing in smallholder farming can be a sustainable way to revitalise agricultural production based on local and diverse food systems. Inclusive agricultural growth has the potential to reduce rural poverty, mitigate the effects of volatile global food prices and boost the domestic economy (IPC-IG 2013).
Keywords: H24; N46; E62; 330; Scale of Institutional Public Procurement; Food; Brazil